Peningkatan Potensi Daerah dan Pemasaran Golok di Desa Kramat Laban Kecamatan Padarincang - Arif Budi Sulistyo (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The purpose of Community Service Programme of “Kuliah Kerja Mahasiswa’ is improving village strength and machete’s marketing in Kramat Laban. The machete’s craftsmen are the object of this community services. By SWOT analysis we could find several problems which is caused by internal weakness and external threat. Method of community services is survey by watching, interview and problem and village potency analysis. The problem such as limited marketing, traditional tools and process, and competition goods with others region. Some proposal and suggestion has been raised and we expect after implemented could result marketing improvement, sale value of machete product, and welfare of craftsmen will be increased and so is Kramat Laban resident.